Educational Environment in the Implementation of Character Education - Cholifah, Siti; Faelasup (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Character education has become a major focus in modern education, with the recognition that the formation of strong character is an important aspect in the formation of quality individuals. The educational environment, which includes schools, parents, communities and technology, plays a crucial role in the implementation of character education. In this abstract, we explore the role of each element of the educational environment in shaping individual character. Schools provide the structure and curriculum that support character learning, while teachers serve as the main agents in providing role models and guidance. Parents play a central role as the primary models for children, while interactions within the community provide important social experiences. Technological developments, while providing wide access to information, also pose new challenges in character building, emphasizing the importance of integrating character values in the use of technology. Collaboration between all these elements of the educational environment is key in creating individuals who have strong, quality character and are able to contribute positively to society. Through holistic understanding and cooperation, it is hoped that positive character building can become a solid foundation for future generations.